DISPENSATION FOR MARRIAGE AT KEPAHIANG RELIGIOUS COURT AFTER THE REVISION OF MARRIAGE LAW NUMBER 1 OF 1974 WITH LAW NUMBER 16 OF 2019 - Yeni Puspitawati; Sirman Dahwal; Akhmad Muslih (Universitas Bengkulu, 2022)
This study raised the issue of the factors causing the increase in marriage dispensation cases at Kepahiang Religious Court after the revision of Marriage Law Number 1 of 1974 with Law Number 16 of 2019. It investigated how the process of examining cases of marriage dispensation applications and the consequences of what laws resulted in the changes of Law Number 16 of 2019 concerning marriage at the Kepahiang Religious Court. To answer this problem, empirical juridical research was used with data obtained through in-depth interviews with the chairman, judges, and court clerks as informants and supporting data in the form of literature books, and laws and regulations, all of which are related to the problem. After the data can then be analyzed based on qualitative juridical analysis. There were several results in this research. First, the factors causing the increase in marriage dispensation cases at the Kepahiang Religious Court were due to promiscuity, parental concerns for their children, and low education factors. Second, the process of examining marriage dispensation cases was carried out by a single judge. The applicants were obliged to present the child, the prospective husband/wife, and the parents/guardian of the prospective husband/wife. Moreover, it was also the language method of the judge that was easy to understand by the child, the time when the judge and clerks did not wear trial attributes when the examination happened, and the availability of advice and the child's statement. Third, the legal consequences resulting from the amendment to Law Number 16 of 2019 are based on some aspects namely, the increase in marriage dispensation cases, the complexity of the process of handling marriage dispensation cases because many requirements had to be fulfilled and many people carried out the underhand marriages.